Dampak Media Sosial Dan Gaya Hidup Terhadap Keputusan Berkunjung Halal Tourism Kota Padang - Selvi Aulia Putri; Sophan Sophian (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine the impact of social media and lifestyle on the decision to visit halal tourism in the city of Padang, this research is a quantitative study, the sampling method uses accidental sampling with a total of 108 respondents. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that social media has a positive and significant impact on visiting decisions with a t-count value greater than t-table (4.429> 1.659), and lifestyle has a positive and significant impact on employee performance with a t-count value greater than t -table (4.249>1.659).